Fallen Angels or Risen Apes? A Tale of the Intricate Complexities of Imbalanced Immune Responses in the Pathogenesis and Progression of Immune-Mediated and Viral Cancers - Ondondo, Beatrice O. (Frontiers in Immunology, 2014)
Excessive immune responses directed against foreign pathogens, self-antigens or commensal microflora can cause cancer establishment and progression if the execution of tight immuno-regulatory mechanisms fails. On the other hand, induction of potent tumour antigen-specific immune responses together with stimulation of the innate immune system is a pre-requisite for effective antitumour immunity, and if suppressed by the strong immuno-regulatory mechanisms can lead to cancer progression. Therefore, it is crucial that the inevitable co-existence of these fundamental, yet conflicting roles of immune-regulatory cells is carefully streamlined as imbalances can be detrimental to the host. Infection with chronic persistent viruses is characterised by severe immune dysfunction resulting in T cell exhaustion and sometimes deletion of antigen-specific T cells. More often this is due to increased immuno-regulatory processes which are triggered to down-regulate immune responses and limit immunopathology. However, such heightened levels of immune disruption cause a concomitant loss of tumour immune-surveillance and create a permissive microenvironment for cancer establishment and progression, as demonstrated by increased incidences of cancer in immunosuppressed hosts. Paradoxically, while some cancers arise as a consequence of increased immuno-regulatory mechanisms that inhibit protective immune responses and impinge on tumour surveillance, other cancers arise due to impaired immuno-regulatory mechanisms and failure to limit pathogenic inflammatory responses. This intricate complexity, where immuno-regulatory cells can be beneficial in certain immune settings but detrimental in other settings underscores the need for carefully formulated interventions to equilibrate the balance between immuno-stimulatory and immuno-regulatory processes.